'waiting for godot' and 'endgame' - Connor, Steven ([S.l.] : Palgrave MD, 1992)
This text gathers together interpretations of Beckett's best-known plays, illustrating a range of theoretical approaches from deconstruction to reader-response theory, psychoanalysis and feminism. Included, as well, is an introduction by Steven Connor, assessing the mutual relations between Beckett's work and contemporary literary theory. There are also introductory notes to the essays. The essays are contibuted by: Mary Bryden, James Calderwood, Steven Connor, Jane Hale, Sylvie Henning, Wolfgang Iser, Andrew Kennedy, Paul Lawley, Jeffrey Nealon, Judith Roof, and Gabriele Schwab. Steven Connor has written books on Dickens, Beckett and Postmodernist Culture.